Meningococcal Serogroup A, C, W(135) and Y Conjugated Vaccine: A Cost-Effectiveness Analysis in the Netherlands - Hepkema, Hiltsje (Public Library of Science, 2013)
BACKGROUND: In 2002, vaccination with a serogroup C meningococcal conjugate vaccine (MenC) was introduced in the Netherlands for all children aged 14 months. Despite its success, herd immunity may wane over time. Recently, a serogroup A,C,W135,Y meningococcal conjugate vaccine (MenACWY) was licensed for use in subjects of 12 months of age and above. OBJECTIVES: To evaluate the cost-effectiveness of meningococcal vaccination at 14 months and an additional vaccination at the age of 12 years, both with the MenACWY vaccine. METHODS: A decision analysis cohort model, with 185,000 Dutch newborns, was used to evaluate the cost-effectiveness of different immunization strategies. For strategies including a vaccination at 12 years of age, an additional cohort with adolescents aged 12 years was followed. The incremental cost-effectiveness ratio (ICER) was estimated for the current disease incidence and for a scenario when herd immunity is lost. RESULTS: Vaccination with MenACWY at 14 months is cost-saving. Vaccinating with MenACWY at 14 months and at 12 years would prevent 7 additional cases of meningococcal serogroup A,C,W135,Y disease in the birth cohort and adolescent cohort followed for 99 years compared to the current vaccine schedule of a single vaccination with MenC at 14 months. With the current incidence, this strategy resulted in an ICER of €635,334 per quality adjusted life year. When serogroup C disease incidence returns to pre-vaccination levels due to a loss of vaccine-induced herd-immunity, vaccination with MenACWY at 14 months and at 12 years would be cost-saving. CONCLUSIONS: Routine vaccination with MenACWY is cost-saving. With the current epidemiology, a booster-dose with MenACWY is not likely cost-effective. When herd immunity is lost, a booster-dose has the potential of being cost-effective. A dynamic model should be developed for more precise estimation of the cost-effectiveness of the prevention of disappearance of herd immunity.